An Ecological Assessment of Invasive Alien Plant Species in Jokhar Lake Area of Kailali District, Nepal - Pant, Gunanand; Thapa, Lal B; Bist, Anita (AMC Journal (Dhangadhi), 2023)
Invasive alien plant species (IAPS) have been creating adverse impacts on native diversity. Diversity of Nepal’s wetland ecosystems are also threatened by several IAPS but the related studies are very scarce. This study has assessed the status of IAPS found in Jokhar Lake of Kailali district, Nepal. The IAPS survey was carried out by sampling 30 plots of (1×1)m2 each in and around the lake area. A total of 17 species of IAPS were reported from the study site. Most of the IAPS were the members of the family Asteraceae. The diversity of IAPS in the lake represents about 65% of the total IAPS in Nepal. Around the lake periphery, Ageratum houstonianum and Argemone mexicana and inside the lake Eichornia crassipes and Pistia stratiotes were major IAPS. The natural beauty of the lake has been ruined by these IAPS. A detailed study on the impacts and ecology of these IAPS in the lake and lake periphery is still lacking. Hence, it is recommended that the IAPS in the lake area should be controlled to conserve the native diversity and the natural beauty of the lake.